IDOLATRIA E CONQUISTA: Estudo do conceito de Idolatria na obra de Juan Ginés de Sepúlveda Democrates Alter Tratado de las Justas Causas de la Guerra contra los Indios e sua controvérsia travada com Frei Bartolomé de Las Casas . - Jesus, Juarez Ferreira de (2010)
Slightly more than half a century after the discovery of the New World, Spanish Conquest in full, would take place in Valladolid in 1550 and 1551, an unprecedented event: a public debate starring two remarkable characters, namely, the Dominican Friar Bartolome de Las Casas and Juan Gines de Sepulveda. This debate is known in history as the Controversy of Valladolid, and had as main objective, to discuss how the Indians of the New World would be treated, what were their rights and their responsibilities. This thesis discusses the context in which this controversy took place, its characters and, of course, itself, in its arguments, exposure mode and constituent structure.(AU)